Synthèse de l’entretien avec Le président CVD, intervenants dans la médiation et la gestion des conflits - Traoré, Seydou; Sanon, Boukary (Criminal justice institutions and the social trajectories of adolescents/youth in Burkina Faso: endogenous/local forms and patterns of punishment, 2021)
This interview summary was produced following a group interview held on 10/ 05 /2021 in Balla with a CVD representative, and a mediation and conflict management practitioner. During this interview, the participants discussed the typology of fault, as well as its management for both modern justice actors and traditional judicial bodies. The discussion also looked at the perception of punishment as a function of gender and social class, the meaning of mediation, and collaboration between traditional and modern institutions in the management of fault.
Keywords: Administration of Justice; Teenagers; Youth; Punishment; Maintenance; Mediation; Conflict management; Conseil Villageois de Développement